2011
DOI: 10.1038/npp.2011.219
|View full text |Cite
|
Sign up to set email alerts
|

The Methylazoxymethanol Acetate (MAM-E17) Rat Model: Molecular and Functional Effects in the Hippocampus

Abstract: Administration of the DNA-alkylating agent methylazoxymethanol acetate (MAM) on embryonic day 17 (E17) produces behavioral and anatomical brain abnormalities, which model some aspects of schizophrenia. This has lead to the premise that MAM rats are a neurodevelopmental model for schizophrenia. However, the underlying molecular pathways affected in this model have not been elucidated. In this study, we investigated the molecular phenotype of adult MAM rats by focusing on the frontal cortex and hippocampal areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 73 publications
6
42
0
Order By: Relevance
“…Consistent with the proteomic data, pathway analysis of the hippocampal metabolites demonstrated that the most significant canonical pathway affected by prenatal MAM administration was the glutamatergic system. Specifically, changes in glutamate, N-acetyl aspartyl glutamate and overlapping spectra of glutamate/glutamine were observed.Taken together, the study by Bahn and colleagues (Hradetzky et al, 2011) further validates the MAM-treated rat as a model relevant to human disease, and extends this work to demonstrate that gestational MAM administration significantly alters glutamatergic markers throughout the hippocampus, in accord with human studies demonstrating alterations in hippocampal function (Konradi et al, 2011; …”
supporting
confidence: 62%
See 3 more Smart Citations
“…Consistent with the proteomic data, pathway analysis of the hippocampal metabolites demonstrated that the most significant canonical pathway affected by prenatal MAM administration was the glutamatergic system. Specifically, changes in glutamate, N-acetyl aspartyl glutamate and overlapping spectra of glutamate/glutamine were observed.Taken together, the study by Bahn and colleagues (Hradetzky et al, 2011) further validates the MAM-treated rat as a model relevant to human disease, and extends this work to demonstrate that gestational MAM administration significantly alters glutamatergic markers throughout the hippocampus, in accord with human studies demonstrating alterations in hippocampal function (Konradi et al, 2011; …”
supporting
confidence: 62%
“…Taken together, the study by Bahn and colleagues (Hradetzky et al, 2011) further validates the MAM-treated rat as a model relevant to human disease, and extends this work to demonstrate that gestational MAM administration significantly alters glutamatergic markers throughout the hippocampus, in accord with human studies demonstrating alterations in hippocampal function (Konradi et al, 2011; …”
supporting
confidence: 62%
See 2 more Smart Citations
“…Cellular disarray in the CA1 region of hippocampus has also been described and is thought to be analogous to hippocampal disarray seen in schizophrenia patients 120,166 . Recently, we carried out a proteomic and metabonomic investigation which showed that MAM-E17 rats have primarily deficits in hippocampal glutamatergic neurotransmission, as seen in some schizophrenia patients 167 . Most importantly, these results were consistent with our finding of functional deficits in glutamatergic neurotransmission, as identified using electrophysiological recordings.…”
Section: Interruption Of Neurogenesismentioning
confidence: 99%